Association Between Self-Reported Dyspnea and Depressive Symptoms in New Mexico Uranium Workers. Issue 3 (May 2021) - Sharma, Shiva; Crisanti, Annette; Kesler, Denece; Shore, Xin W.; Vlahovich, Kevin; Sood, Akshay
Abstract : New Mexico has the largest number of former uranium workers, mostly racial/ethnic minorities. Uranium workers are at risk for dyspnea secondary to mine dust exposure. The association between dyspnea and depressive symptoms has not been well examined in occupational minority cohorts. This study evaluated the associations between dyspnea (measured by the modified Medical Research Council Questionnaire) and depressive symptoms (measured by the Patient Health Questionnaire-2) in former uranium workers screened by the New Mexico Radiation Exposure Screening & Education Program. The subjects were mostly elderly, rural-residing, minority males. Dyspnea was commonly reported; however, depressive symptoms were uncommon. At baseline, former workers experiencing higher levels of dyspnea were more than 3 times likely to endorse depressive symptoms than those with no or mild dyspnea. Longitudinal analysis failed to determine an association between change in dyspnea and concomitant change in depressive symptoms. Dyspnea and depressive symptoms were associated cross-sectionally in former uranium workers.